2017
DOI: 10.1126/science.aan3174
|View full text |Cite
|
Sign up to set email alerts
|

Glia relay differentiation cues to coordinate neuronal development in Drosophila

Abstract: Neuronal birth and specification must be coordinated across the developing brain to generate the neurons that constitute neural circuits. We used the Drosophila visual system to investigate how development is coordinated to establish retinotopy, a feature of all visual systems. Photoreceptors achieve retinotopy by inducing their target field in the optic lobe, the lamina neurons, with a secreted differentiation cue (Epidermal Growth Factor; EGF). We find that communication between photoreceptors and lamina cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
112
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(122 citation statements)
references
References 31 publications
(72 reference statements)
8
112
0
Order By: Relevance
“…Previous gene expression studies in the developing optic lobe revealed that among the eight dilp genes, dilp6 is expressed in glia cells in Drosophila (Fernandes et al, 2017;Okamoto and Nishimura, 2015;Rossi and Fernandes, 2018;Sousa-Nunes et al, 2011). By using Gal4 lines, dilp6 expression in the surface and cortex glia was observed at all developmental stages ( Figures 6B and S6A-S6I).…”
Section: Glial Cell Insulin Signal Is Critical For Gogo Phosphorylationmentioning
confidence: 75%
See 1 more Smart Citation
“…Previous gene expression studies in the developing optic lobe revealed that among the eight dilp genes, dilp6 is expressed in glia cells in Drosophila (Fernandes et al, 2017;Okamoto and Nishimura, 2015;Rossi and Fernandes, 2018;Sousa-Nunes et al, 2011). By using Gal4 lines, dilp6 expression in the surface and cortex glia was observed at all developmental stages ( Figures 6B and S6A-S6I).…”
Section: Glial Cell Insulin Signal Is Critical For Gogo Phosphorylationmentioning
confidence: 75%
“…The Drosophila insulin receptor (DInR), a tyrosine kinase receptor, is one of the kinases that phosphorylate the YYD motif of Gogo (Mann et al, 2012). A growing number of recent studies have revealed the functional involvement of DInR in nervous system development (Fernandes et al, 2017;Rossi and Fernandes, 2018;Song et al, 2003). The current study was able to examine stepwise R8 axonal targeting events across development by following protein localization and by specifically controlling Gogo and Fmi levels in R8 axons.…”
Section: Introductionmentioning
confidence: 99%
“…One supporting evidence for this model is the lack of cell death of lamina neurons in DIP mutants (Xu et al, 2018a). Lamina differentiation is directly induced by photoreceptors R1-6 axons (Huang and Kunes, 1996), thus induction of the lamina by R1-6 allows the numerical matching of lamina cartridges and ommatidia, and the production of the right number of lamina neurons in each cartridge (Fernandes et al, 2017). This might explain why some neurons do not require target-derived trophic supports for their survival.…”
Section: Apoptosis As a Mechanism For Numerical Matching Of Neuronal mentioning
confidence: 95%
“…The only exception can be seen for the midline glia which instruct the growth of commissural axons across the CNS midline by expressing the two guidance cues, Netrin and Slit (Howard et al, ). Drosophila glial cells, however, participate in the adjustment of optic centers where they relay a signal from photoreceptors to induce lamina neuronal differentiation (Fernandes et al, ). Glial cells are also involved in regressive events and have some important roles during pruning.…”
Section: Conservation Of Processesmentioning
confidence: 99%